Different Degree Centrality Changes in the Brain after Acupuncture on Contralateral or Ipsilateral Acupoint in Patients with Chronic Shoulder Pain: A Resting-State fMRI Study. (25th April 2020) - Yan, Chao-Qun; Huo, Jian-Wei; Wang, Xu; Zhou, Ping; Zhang, Ya-Nan; Li, Jin-ling; Kim, Mirim; Shao, Jia-Kai; Hu, Shang-Qing; Wang, Li-Qiong; Liu, Cun-Zhi
Abstract : Chronic shoulder pain (CSP) is the third most common musculoskeletal problem. For maximum treatment effectiveness, most acupuncturists usually choose acupoint in the nonpainful side, to alleviate pain or improve shoulder function. This method is named opposite needling, which means acupuncture points on the right side are selected for diseases on the left side and vice versa. However, the underlying neural mechanisms related to treatment are currently unclear. The purpose of this study was to determine whether different mechanisms were observed with contralateral and ipsilateral acupuncture at Tiaokou (ST 38) in patients with unilateral CSP. Twenty-four patients were randomized to the contralateral acupuncture group (contra-group) and the ipsilateral acupuncture group (ipsi-group). The patients received one acupuncture treatment session at ST 38 on the nonpainful or painful sides, respectively. Before and after acupuncture treatment, they underwent functional magnetic resonance scanning. The treatment-related changes in degree centrality (DC) maps were compared between the two groups. We found alleviated pain and improved shoulder function in both groups, but better shoulder functional improvement was observed in the contra-group. Increased DC in the anterior/paracingulate cortex and decreased DC in bilateral postcentral gyri were found in the contra-group, while decreased DC in the bilateral cerebellum and right thalamus was observed in the ipsi-group. Furthermore, the DC value in the bilateral anterior/paracingulate cortex was positively correlated with the treatment-related change in the Constant–Murley score. The current study reveals different changes of DC patterns after acupuncture at contralateral or ipsilateral ST 38 in patients with CSP. Our findings support the hypothesis of acupoint specificity and provide the evidence for acupuncturists to select acupoints for CSP.